The importance of intellectual capital in the company (Journal of Universal Excellence, 2026)
Research Question (RQ): This article explores the importance of intellectual capital in the company.Purpose: To determine what is the importance of intellectual capital in businesses in the current economic climate.Method: As a research method I used descriptive method, and review of the literature in the form of articles and books. Below I summarize important observations and insights.Results: Intellectual capital has a significant and positive impact on the business performance of the company, but it is underestimated.Organization: The research contributes to a better achievement of business performance.Society: Better business contributes to the wider environment, as this will also ensure stability of the organization.Originality: A different perspective on the importance of intellectual capital. There are not a lot of transparent articles on this topic.Limitations/Future Research: Limitation of the study is that we have discussed only a certain number of resources.
Keywords: intellectual capital; human capital; structural capital; relational capital; operational performance; employee training; knowledge